CODE-SWITCHING IN EFL CLASSROOM BY ENGLISH TEACHER OF SMP NEGERI 2 REMBANG (RETAIN, 2015)
Abstract This study deals with teacher’s code-switching of teacher talk in EFL classroom. The objectives of this study are: (1) to find out the types of code-switching used by the teacher and its function, (2) to investigate the teacher’s reason in using code-switching, and (3) to investigate find out the student’s attitude towards teacher’s code-switching. This research is designed in descriptive qualitative research. An English teacher and her students of seventh graders in SMP Negeri 2 Rembang were observed during class session and recorded. The classroom talks that have been recorded was transcribed and analysed by the researcher to find out the answers of the first research questions. Moreover, audio interview was also employed to answer the second and third research questions. The result of this study shows that there were three types of code-switching used by the teacher namely tag-switching, inter-sentential switching and intra-sentential switching. Also, the teacher’s reason of using code-switching was explaining material, creating humor, conveying meaning and creating intimacy. In addition, dealing with this code-switching, student obviously have positive attitude and agreed that it brings a positive effect to them. Keywords: Teaching English as Foreign Language, Teacher Talk, Code-Switching Abstrak Penelitian ini berhubungan penggunaan alih kode dalam percakapan guru di kelas bahasa Inggris sebagai bahasa asing. Tujuan penelitian ini diantaranya adalah: (1) melacak tipe alih kode yang digunakan oleh guru dan fungsinya (2) melacak alasan guru dalam menggunakan alih kode, (3) mengetahui sikap murid menyikapi alih kode yang digunakan oleh guru. Penelitian ini menggunakan penelitian deskriptif kualitatif sebagai desain penelitian.Seorang guru bahasa inggris dan sejumlah siswa kelas VII di SMP Negeri 2 Rembang telah diobservasi dan direkam selama proses belajar mengajar untuk menjawab pertanyaan penelitian yang pertama. Cek list dan wawancara juga digunakan untuk menjawab pertanyaan yang kedua dan ketiga. Hasil penelitian menunjukkan bahwa guru menggunakan tiga jenis alih kode: tag-switching, inter-sentential switching, dan intra-sentential switching. dan alasan guru menggunakan alih kode adalah untuk menjelaskan materi, menciptakan humor, menjelaskan arti kata sulit, dan untuk kedekatan dengan murid. Dan terakhir, menghadapi alih kode guru, murid menyikapinya dengan positif dan percaya bahwa alih kode memberikan efek positif untuk mereka. Kata Kunci: Pengajaran bahasa Inggris untuk bahasa asing, Percakapan guru, Alih kode